2020
DOI: 10.2196/20776
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Walking Activity in Patients With Systolic Heart Failure Equipped With a Step Counter: Randomized Controlled Trial

Abstract: Background Physical activity has been shown to decrease cardiovascular mortality and morbidity. Walking, a simple physical activity which is an integral part of daily life, is a feasible and safe activity for patients with heart failure (HF). A step counter, measuring daily walking activity, might be a motivational factor for increased activity. Objective The aim of this study was to examine the association between walking activity and demographical and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, physical capacity or physical activity can be measured by other methods. In a RCT with patients with HF enrolled in a telerehabilitation program, Gade et al [ 24 ], whose study was not included in this review, measured physical activity using a Fitbit step counter for 1 year. The study found no increase in the number of steps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, physical capacity or physical activity can be measured by other methods. In a RCT with patients with HF enrolled in a telerehabilitation program, Gade et al [ 24 ], whose study was not included in this review, measured physical activity using a Fitbit step counter for 1 year. The study found no increase in the number of steps.…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant correlation was found between the increased number of steps and the reduction in the ejection fraction. Furthermore, it was found that a step counter can be a useful tool to help patients monitor their own physical activity [ 24 ]. These findings suggest that measurement of patients’ physical activity can be carried out using technologies such as a step counter instead of tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, older adults with HF often suffer from frailty and fatigue; therefore, it may be harder for them to reach the optimal step levels. In a recent study that examined the walking activity of adults with HF using a step counter over a year, younger age, higher ejection fraction, and lower HF classification were found to be significantly correlated with the number of daily steps [ 68 ]. Whether modest increases in steps result in health benefits among older adults with HF remains to be seen and may signify a need for additional supportive or palliative interventions that relieve physical or mental symptom burden to ensure optimal quality of life among patients with HF [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other types of technologies used were different types of ECG recorders, blood pressure meter, weight scale, saturation device, respirometer video, oximeter sphygmomanometer, computer, and others (Table 1) [7,[13][14][15][16][17][18][19][20][21][22][23]. However, other studies on telerehabilitation use among patients with HF and patients with other cardiac disorders utilized technologies such as pedometers, sleep sensors, tablets, online portals, and apps [24][25][26]. This suggests that other studies will employ additional, more advanced, and newer technologies than the ones mentioned in this review, such as wearables.…”
Section: Principal Findingsmentioning
confidence: 99%